2017
DOI: 10.1007/s10151-017-1593-0
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of injectable bulking agents for fecal incontinence: a systematic review and meta-analysis

Abstract: Administration of injectable bulking agents results in significant midterm improvement in FIS. Perianal injection route and implants intact on EAUS were predictive of higher improvement in incontinence. However, given the paucity of randomized controlled trials in the literature, further research is needed to improve the quality of the evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Analysis of the literature revealed five systematic reviews which assessed the effects of injectable bulking agents versus no injectable bulking agents on FI complaints in the general FI population 76–80 . In total two of the RCTs included in the systematic reviews answer the PICO question by assessing the effects of injectable bulking agents compared to a control (sham).…”
Section: Second Line: Surgical Interventions For Faecal Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the literature revealed five systematic reviews which assessed the effects of injectable bulking agents versus no injectable bulking agents on FI complaints in the general FI population 76–80 . In total two of the RCTs included in the systematic reviews answer the PICO question by assessing the effects of injectable bulking agents compared to a control (sham).…”
Section: Second Line: Surgical Interventions For Faecal Incontinencementioning
confidence: 99%
“…Conclusion: SNM ON generally results in fewer mean number of weekly FI episodes compared to SNM OFF and compared to conservative treatment (significantly in 3/5 studies, no significance reported in one study and no difference in one study). Severity of FI was also generally less in the SNM group (Significantly less in two-fifths studies, Analysis of the literature revealed five systematic reviews which assessed the effects of injectable bulking agents versus no injectable bulking agents on FI complaints in the general FI population [76][77][78][79][80]. In total two of the RCTs included in the systematic reviews answer the PICO question by assessing the effects of injectable bulking agentscompared to a control (sham).…”
mentioning
confidence: 99%
“…Secondly, as previously stated, FI is a symptom with multiple etiologies indicating that most treated cohorts are heterogenous [2,[5][6][7][8]. Finally, there are at least 11 bulking agents on the market, and site, volume, route and method of injection differ from study to study [9,31]. A 2013 Cochrane review concluded that the quality is poor in most trials, adding to the challenge [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies have found that manometry findings did not correlate consistently with AI severity; however, manometry findings may influence the management and individual selection of therapeutic strategies. [22][23][24][25][26]…”
Section: Between-group Analysis Of Anorectal Manometry Datamentioning
confidence: 99%